Development of Engineering for the Craft Industry of Women’s Outer Clothing in Blacu (International Journal of Scientific Research and Management (IJSRM), 2023)
The engineering development of the outerwear industry is a creative research conducted in the Medan area, Indonesia. This research applies explosives qualitative method in producing new products. Creativity in the development of outerwear craft industry engineering, as follows: 1) Craft industry engineering learning is carried out online in the delivery of theoretical studies; 2) concept map; 3) drawing sketches; 4) motif design and outer clothing; 5) manufacture of women’s outerwear; 6) fashion art presentation. Thus the creative activities of the women’s outerwear craft industry can be useful for the younger generation in developing knowledge and skills in the field of textile and fashion craft with the hope that the younger generation will be able to become independent entrepreneurs.